The Multiple Dimensions of Managerial Networking. (May 2013) - Torenvlied, René; Akkerman, Agnes; Meier, Kenneth J.; O'Toole, Laurence J.
Studies in public management show that agencies draw different types of support from different actors and organizations in their environment. If this is true, we would expect that managers differentiate their networking activity toward different types of external actors and organizations. However, empirical studies of the networking activities of managers do not reveal such a differentiation: these studies consistently report the existence of only one factor of managerial networking activity. The present article aims to solve this puzzle by disaggregating managerial networking into multiple scales of managerial networking activity, each related to a specific type of support from the agency's environment. A cumulative scaling analysis of the network ties of Texas school district superintendents for the years 2002 and 2005 shows the existence of three such stable and homogeneous networking scales, respectively, providing (a) political support, (b) bureaucratic coping, and (c) coproduction. We compare these results with those of the method used in previous studies: factor analysis. We illustrate the potential of cumulative scaling for the analysis of managerial networking by comparing the effect of the managerial networking factor with those of the three networking scales on the pass rates of Latino students on the Texas Assessment of Academic Skills. The article concludes with a discussion of the implications for our understanding of managerial networking.